Efeitos da Leucena e da adubação NPK sobre a cultura do feijão no Cerrado - Chagas , José Mauro; Pereira Filho , Israel A; Vieira , Clibas (Revista Ceres, 2025)
An experiment was carried out in a poor «cerrado» soil at Patrocínio, state of Minas Gerais, in order to determine the effect of Leucaena leucocephala, as a green manure, and chemical fertilization on the yield of beans (Phaseolus vulgaris).